The Effect of Storage Periods of Teak (Tectona grandis) Bud in the Sheath of Banana to the Succesfulness of Budding - Sari Pangastuti; Afif Bintoro; Duyat Duryat (Jurnal Sylva Lestari, 2018)
Teak (Tectona grandis) is one of comercial plant which has good quality of wood and has high economic value. The enhancement and improvement of teak cultivation techniques was need to be done to fulfill the demands of teak wood. Budding was one of cultivation technique that combine the generative and vegetative propagation technique, so that the benefits of both technique could be obtained at once. The obstacles of budding technique were about the buds storage and distribution. The aim of the experiment were to determine the effectiveness of banana sheath in maintain the viability of teak buds and to determine the maximum periods of teak buds storage. A randomized completely block was employed as an experiment design with two groups and four treatments. The first group was the storage out of banana sheath bag, and the second group was the storage inside of with banana sheath bag. Four periods of storage were used as treatment consist of 0 day of storage (Y0), 2 days of storage (Y1), 4 days of storage (Y2), and 6 days of storage (Y3). Data were analyzed using ANOVA with further testing using LSD on the level of significance 5%. The result showed that the storage of teak buds inside the banana sheath bag and stored up to six days were be able to maintain the percentage of budding for 66,67%, and the storage up to four days were be able to maintain the bud viability, the percentage of budding life, the average days of the bud to sprout, and the number of leaves that as well as the buds which is budding without stored. Keywords : banana sheath, budding, teak